Meningkatkan Kedisiplinan Kerja Karyawan Melalui Kompensasi, Kepemimpinan Dan Lingkungan - Sutianingsih Sutianingsih; Yuliyana Yuliyana (Universitas Slamet Riyadi, 2023)
To realize organizational goals, high discipline from all elements of the organization is required. This study aims to determine the effect of compensation, leadership and work environment on employee work discipline. This research is a quantitative study. The population as well as the sample are employees at a notary office. The sampling technique uses a saturated sampling technique with a sample size of 33 employees. Research instruments with questionnaires are tested with validity and reliability tests and classical assumption tests. Data analysis method with multiple linear regression test. Based on the results of the study showed that compensation has a significant effect on work discipline, leadership has a significant effect on employee work discipline, and the work environment does not have a significant effect on employee work discipline. Leadership has the greatest influence on the work discipline of employees. Keywords: compensation, leadership, work environment and discipline